An Impact Study on the Level of Employment and Revenues Towards the Adoption of Payment Model in the Retail Industry in Guangdong, China - Zhou, Haixia (International Journal of Global Economics and Management, 2024)
This descriptive-correlational study investigated the relationship between mobile payment adoption and its impact on employment and revenue growth in the retail sector. The study surveyed 300 retailer-respondents across Guangdong Province to assess the adoption rate of mobile payment systems, merchant satisfaction, and transaction frequency, and how these factors correlated with job creation and revenue growth. The findings revealed a significant relationship between adoption rate and job creation and revenue growth, highlighted the positive effects of mobile payment adoption on business performance. These insights provided valuable information for retailers in the region, suggesting that increasing adoption rates can lead to enhanced business outcomes, while emphasizing the importance of improving customer experience and personalized engagement strategies for long-term success.